A study of the legislative framework governing rehabilitation and assistive robots in Malaysian healthcare institutions: a comparison with the United States / Nurus Sakinatul Fikriah Mohd Shith Putera - Mohd Shith Putera, Nurus Sakinatul Fikriah (2017)
Rehabilitation and assistive robots used in rehabilitation therapy programmes and for personal care, is a newly emerging collaborative effort between medical and robotic studies. This robotic evolution is being keenly felt in Malaysia, precisely in responding to community with neurodevelopmental disorders such as Autism Spectrum Disorders (ASD) and Cerebral Palsy. Nevertheless, the closer proximity of humans and robots demonstrates the risk of exposing human subjects to the unpredictable robotic behaviour and thus, the issue of safety becomes central. Consequently, the interaction motivates this research to revisit the adequacy of the current legislative framework in governing rehabilitation and assistive robots in comparison with the United States. The novel challenges related to rehabilitation and assistive robots result with the inadequacy of the current legislative framework to govern the risk arising from such technology. This problem revolves around two concerns namely the incompatibility of the traditional theories of liability, and the vagueness of the scope of the Medical Device Act 2012 to govern rehabilitation and assistive robots. The objectives of this research are achieved by adopting the doctrinal methodology of data collection and data analysis focusing on the comparative, interpretational, analogy, historical and jurisprudential approaches. The findings of the research concluded that the law lags behind technology, the fault-based theory of liability is unworkable for autonomous robots, the difficulty in establishing the element of causation in a strict liability claim, the generalisation of the medical device regulatory framework, the disorganized standards associated with rehabilitation and assistive robots and that the legal personhood model is insignificant to the Malaysian robot regulation. This research contributes in setting forward suggestions and recommendations to improve the current legislative framework, assists in the formulation of national policy and specific law on robots, subsequently benefiting the industrial player, healthcare institutions as well as the community with disabilities. Ultimately, this research contributes to a body of literature on the law of robots.